KESERAGAMAN POLA PEMBANGUNAN SEBAGAI POTRET KETIDAK OTONOMAN PEMERINTAH DESA DALAM PENGELOLAAN DANA DESA - Rudiana M.Si; Dian Fitriani Afifah (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2019)
The village is a customary law community unit that has autonomy in carrying out its government. Village autonomy is biased because villages are positioned as objects of development not as subjects of development. The role of the village as the subject of development means that the village is able to plan, finance and implement governance. The presence of the Village Fund has brought the spirit of change to the village, because the village is required to be able to manage the Village Fund to create an independent and prosperous village. Mandiri does not mean that the village becomes an integral part of the top level government, both central and regional. In fact, the management of the Village Fund in both traditional and modern villages does not create an independent village, because the top level government only makes the village a target or project location (object of development). The practices of uniforming the pattern of development towards the use of the Village Fund have negated the principle of using the Village Fund which is used in accordance with village needs, regional strategies and village typologies. So that the uniformity of the pattern of development that occurs in traditional villages or modern villages is evidence of the lack of autonomy of village governments in the management of Village Funds.